Curtain Raiser. - MARANI, MATTHEW (Architectural Record, 2025)
The article focuses on the new training facility for Ironworkers Local 63, located in Broadview, Illinois, designed by Gensler to enhance the training of ironworkers in Chicago. The 13,500-square-foot building features a striking design with black-tinted glass and precast-concrete panels, accommodating various training activities, including curtain wall installation and welding. Opened in June 2024, the facility serves not only as a training center but also as a community hub, hosting meetings and tours to promote the ironworking trade. The design addresses challenges such as thermal heat gain and structural integrity, ensuring a functional and inspiring environment for future ironworkers.